Do patients and research subjects have a right to receive their genomic raw data?: an ethical and legal analysis - Schickhardt, Christoph; Fleischer, Henrike; Winkler, Eva C. (BMC medical ethics, 2020)
As Next Generation Sequencing technologies are increasingly implemented in biomedical research and (translational) care, the number of study participants and patients who ask for release of their genomic raw data is set to increase. This raises the question whether research participants and patients have a legal and moral right to receive their genomic raw data and, if so, how this right should be implemented into practice.
Gesehen am 27.04.2020